2015
DOI: 10.1080/21645515.2015.1041687
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent decrease of anti-HBs titers and effect of booster doses using 2 different vaccines in Palestinian children vaccinated in early childhood

Abstract: Immunization against hepatitis B virus (HBV) has proven to be highly effective and led to significant reduction of new infections worldwide. However, protective immunity measured by anti-HBs titers may decrease to critical levels in the years after basal immunization, particularly in case of exposure to HBV variants different from the vaccine strain. We tested 400 Palestinian children between one and 19 years of age for their anti-HBs titer, challenged the immune memory of those with low or absent anti-HBs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 47 publications
1
19
1
1
Order By: Relevance
“…Figure clearly indicates that the protective levels waned with increasing age between 1 and 8 years old, the percentage of lower concentrations declined more rapidly and that of higher titres kept relatively stable, especially the rate of high‐responders without showing obvious increasing or decreasing trend, suggesting that high antibody levels may be maintained for longer. Some studies also demonstrated that antibody levels showed a significant decline in children after hepatitis B vaccination in infancy . The decline of antibody concentrations may be associated with hepatitis B vaccine type, dosage, different vaccination programmes, physical quality and vaccination age …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure clearly indicates that the protective levels waned with increasing age between 1 and 8 years old, the percentage of lower concentrations declined more rapidly and that of higher titres kept relatively stable, especially the rate of high‐responders without showing obvious increasing or decreasing trend, suggesting that high antibody levels may be maintained for longer. Some studies also demonstrated that antibody levels showed a significant decline in children after hepatitis B vaccination in infancy . The decline of antibody concentrations may be associated with hepatitis B vaccine type, dosage, different vaccination programmes, physical quality and vaccination age …”
Section: Discussionmentioning
confidence: 99%
“…Some studies also demonstrated that antibody levels showed a significant decline in children after hepatitis B vaccination in infancy. [14][15][16] The decline of antibody concentrations may be associated with hepatitis B vaccine type, dosage, different vaccination programmes, physical quality and vaccination age. [17][18][19][20] Surprisingly, the proportion of protected anti-HBs titres slowly increased for children older than 8 years old, and the trend in antibody levels for children aged 9-16 declined compared to that in the 1-9 age groups, being >10 mIU/mL and of >100 mIU/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors influencing the effectiveness of the vaccination. Some studies found that antibody levels showed a significant decline in children after HB vaccination in infancy [36][37][38]. One potential reason may be vaccination age [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, both anti-HBs seroconversion rates and anti-HBs GMCs in T6 after the third booster dose increased rapidly in T7. So, the significant difference about the increased aspect of seroconversion rate and GMCs between T1 and T7 and the rapid decrease in T6 despite two dose vaccination are related with reminding, anti-HBs titer before vaccination and the checking time of anti-HBs rather than the number of reminding doses (17,32,33).…”
Section: Discussionmentioning
confidence: 99%